Superficial Vein Thrombosis of Lower Limbs: Influence of Factor V Leiden, Factor II G20210A and Overweight - Moerloose, Philippe de; Wutschert, Robert; Heinzmann, Monica; Perneger, Thomas; Reber, Guido; Bounameaux, Henri (Thrombosis and Haemostasis, 1998)
Superficial vein thrombosis (SVT) has been reported in patients with thrombophilia. In the present unmatched case-control study, the two most common thrombophilic abnormalities (factor V Leiden and factor II G20210A) were searched for in 112 consecutive patients with SVT of lower limbs and in 180 healthy donors. FV Leiden was present in 16/112 (14.3%) SVT patients and 11/180 (6.1%) controls (odds ratio 2.51, 95% CI 1.04-6.24) and FII G20210A in 4/112 (3.6%) patients and 2/180 (1.1%) controls (OR 3.28, 95% CI 0.46-36.84). In addition, body mass index (BMI) ≥28 kg/m2 was also associated with SVT (OR 2.81, 95% CI 1.60-5.00). After adjustement for BMI ≥28 kg/m2, the association between FV Leiden and SVT remained strong though no longer statistically significant. Among patients with SVT, the presence of FV Leiden was independently associated with the absence of varicose veins (OR 4.62, 95% CI 1.25-18.0) and with a BMI ≥28 kg/m2 (OR 3.74, 95% CI 1.05-15.1). In conclusion, both FV Leiden and overweight seem to predispose to SVT, a finding that should be confirmed in larger studies.